Promoting Healthy Ageing in South Africa Through Vaccination of the Elderly - Sibanda, Mncengeli; Meyer, Johanna C.; Mahlaba, Kesentseng J.; Burnett, Rosemary J. (Frontiers in Public Health, 2021)
The World Health Organization estimates that globally, the proportion of people aged ≥60 years will more than double by the year 2050, with the majority of elderly people living in low- and middle-income countries such as South Africa. Population ageing is an impending public health concern, potentially negatively impacting on South Africa's economy and health system if the government does not adequately prepare for this change. Globally, many potential solutions to ensure healthy ageing are being discussed and implemented, including adopting a “life-course” approach to vaccination which includes vaccination of the elderly, since they are at considerable risk of severe morbidity and mortality from vaccine-preventable diseases. While vaccines are considered as one of the greatest tools for preventing childhood infectious disease morbidity and mortality, they are under-utilised in strategies for promoting healthy ageing in South Africa, where only influenza vaccination is available free of charge to the elderly accessing public sector healthcare. Population ageing coupled with the high incidence of vaccine-preventable diseases amongst elderly South Africans, necessitates establishing a comprehensive national policy and guidelines for vaccination of the elderly.